The Impact of Information Sharing on Supply Chain Performance Mediated by Company Relationships - Muhammad Evan Alhamda; Tri Wahyuningsih (Jurnal Manajemen dan Kewirausahaan, 2023)
MSMEs are the backbone of the Indonesian economy, because they contribute greatly to Indonesia's economic growth. MSMEs snacks have a broad market potential due to increasing public demand and a large variety of products. However, they are still faced with various challenges in terms of supply, such as price volatility of raw materials, limited access to stable supplies, depending on only one supplier, as well as challenges in logistics and distribution. The purpose of this study was to test and see the effect of Information Sharing on  Supply Chain Performance in snack food MSMEs in Klaten Regency mediated   Company Relationships due to the constraints faced by MSMEs  in the supply of raw materials and fulfilling requests. Purposive sampling technique was used to get samples in this study. The PLS analysis method was used in this study. This study has the results: (1) Information Sharing has a positive effect on  Supply Chain Performance, (2) Information Sharing has a positive     effect on  Company Relationships, (3)  Company Relationships has a positive effect on  Supply Chain Performance, (4) Information Sharing has a positive effect on  Supply Chain Performance mediated   Company Relationships.